Critiquing violent crime in the media - Mellins, Maria; Moore, Sarah (Palgrave Macmillan, 2021)
This book explores the recent surge in true crime by critically exploring how murder and violence are represented in documentaries, films, podcasts, museums, novels and in the press, and the effects. From a range of contributors, it touches on a wide variety of topics overall and illustrates how examining true crime across the changing popular media landscape can contribute to important debates in contemporary culture and society. It encourages a critical eye towards understanding the harmful stereotypes, myths and misinformation that popular media can bring. Arranged around four sections, including: true crime trials, representations of victims, the consumption of serial killer narratives, and true crime spaces, each chapter explores different themes and topics across traditional and newer media. These topics include: emotion and appeals for justice in Making a Murderer, #MeToo and misogyny in crime narratives, true crime journalism being exploitative, the ethics of consuming dark tourism and the appetite for true crime, live streamed murder, and the ways in which true murder accounts might lend insight into other types of crime such as domestic violence and stalking. This book stimulates discussion on courses in crime, media and culture as well as in film and media studies, and it also speaks to those with a general interest in true crime.